Átkelőhelyek a Tiszán az Árpád-korban - Weisz Boglárka (Acta Universitatis Szegediensis : acta historica, 2005)
The crossing-places (bridge, ferry, ford) were indispensable in the Middle Ages for travellers to traffic. All the crossing-places on river Tisza were ferries (24 ones) in the charters from the Arpadian period on river Tisza from Szőllős to Becse. There were important ferries by main roads (e. g. Abád), some ferries were used only at stated weather conditions. It is possible that other ferries (Titel, Adorján) were used on river Tisza at the age of the Árpáds, too.